Al and Fe-containing Mn-based layered cathode with controlled vacancies for high-rate sodium ion batteries. (October 2020) - Liu, Xiangsi; Zhong, Guiming; Xiao, Zhumei; Zheng, Bizhu; Zuo, Wenhua; Zhou, Ke; Liu, Haodong; Liang, Ziteng; Xiang, Yuxuan; Chen, Zirong; Ortiz, Gregorio F.; Fu, Riqiang; et al.
Abstract: Mn-based layered oxides as one of the most promising and cost-effective cathode candidates for sodium-ion batteries still face great challenge to achieve high capacity with long cycle life under high-rate current simultaneously. In this work, we propose an effective strategy by a combination of liquid N2 quenching and aliovalent doping to get new layered cathode materials. As evidenced by in-situ synchrotron X-ray diffraction, time-of-flight powder neutron diffraction and solid-state 23 Na nuclear magnetic resonance techniques, the proposed synthesis methods allow tuning the transition metal ions vacancies and enhance Mn 4+ /Mn 3+ redox center of P2-type Mn-based materials. Our results demonstrate that such an optimized structure significantly enhances the deliverable capacity, Na + mobility and electronic conductivity of the materials. Furthermore, the effects of aliovalent doping elements and different cooling approaches on the long-range structure, local environment and electrochemical performance are comprehensively studied by comparing a wide range of doped Na0.67 Mx Mn1-x O2 (M = Li, Mg, Al, Fe) materials. The optimized Na0.67 Al0.1 Fe0.05 Mn0.85 O2 material exhibits a remarkably high initial capacity of 202 mAh g −1 among ever reported P2-type layered oxides within 2–4 V, a stable capacity retention of 81% after 600 cycles and outstanding rate capability of the specific capacity up to 122 mAh g −1 at 1200 mA g −1 . Graphical abstract: Controlling Mn vacancies in Na2/3 Mx Mn1-x O2 cathodes is successfully validated by different cooling rate methods. Liquid N2 quenching offers the best treatment leading to vacancies-free Al 3+ and Fe 3+ co-doped Mn-based layered oxides, which significantly enhances the specific capacity through the control of Mn 4+ /Mn 3+ redox centers, better Na + mobility and electronic conductivity. Image 1 Highlights: Study the effects of different cooling rate and aliovalent doping elements on P2–Na0.67 MxMn1-x O2 materials. Firstly proposing that liquid N2 quenching offers the best treatment leading to vacancies-free Mn-based layered oxides. Cost-effective Na0.67 Al0.1 Fe0.05 Mn0.85 O2 material delivers a remarkable rate capability.